Ternary layered solid acid nanosheet catalyst as well as preparation method and application thereof
Through trace strong acid treatment and organic solvent roll grinding technology, solid acid sites are formed, which solves the problem of catalytic performance reduction caused by etching MAB phase materials in extreme environments, and significantly improves the catalytic performance of alkaline HER.
Patent Information
- Application Number
- CN202411160056.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-02-18
AI Technical Summary
The existing preparation methods of layer-like nanomaterials etching MAB phase materials in extreme environments, resulting in material corrosion, agglomeration, and phase transformation, thereby reducing catalytic performance, especially in alkaline HER catalysis.
The MAB phase precursor was subjected to surface deoxidation layer treatment using trace strong acid, then mixed with organic solvent, mechanical roller milling at room temperature, partially etching the A atomic layer to form solid acid sites, and improve the catalyst in alkaline medium performance.
The acid-like environment is formed through the uniform distribution of acid ions on the surface, which significantly improves the catalytic performance of alkaline HER and is better than the untreated MAB phase precursor and the MAB phase materials after high-temperature strong alkali etching.
Smart Images

Figure CN119465233A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new energy materials, and specifically relates to a ternary layered solid acid nanosheet catalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen energy will play an important role in the future development of green energy replacing fossil fuels due to its advantages of low carbon, safety, high efficiency and cleanliness. Among the many hydrogen production methods, the electrolysis of water to drive hydrogen evolution (HER) driven by renewable energy (hydropower, wind power, solar energy, etc.) is considered to be the most economical and effective way to produce hydrogen. To produce hydrogen through HER, precious metal platinum-based catalysts are usually required to reduce the overpotential of hydrogen production, but the small reserves and high prices of precious metals limit their large-scale application in the field of HER. On the other hand, compared with the traditional acidic environment, the alkaline HER reaction can avoid the acid corrosion of metal electrodes and catalysts, the acid pollution of gas production, and can also be coupled with other chemical reactions, which has a larger scale of application prospects. However, unlike the acidic environment where a large amount of hydrogen protons are available, in the alkaline environment, the hydrogen protons used for the HER reaction need to be generated by the splitting of water molecules, which will undoubtedly introduce additional reaction barriers, thereby increasing the overpotential of the HER reaction. Therefore, it is of great scientific and practical value to develop cheap and efficient alkaline HER electrocatalysts for the inert water splitting step of alkaline HER.
[0003] Due to their flat structure and high specific surface area, layered nanomaterials can induce high surface chemical activity and promote H + Chemical adsorption increases the interfacial charge transfer rate, thereby improving the electrocatalytic performance to replace the commercial platinum (Pt) catalyst in the HER process. However, the traditional preparation methods of existing layered nanomaterials all use high temperature and high pressure strong acid and strong base to completely etch the A atomic layer to obtain 2D MBenes materials. This traditional preparation method will corrode the MBenes layer, and the A atomic layer will be completely etched, resulting in the loss of solid acid sites on the surface of the material. At the same time, etching under high temperature and high pressure conditions will cause phase change and agglomeration growth of the material, thereby reducing the alkaline HER catalytic performance of the 2D MBenes material. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a ternary layered solid acid nanosheet catalyst and a preparation method thereof, aiming to solve the problems of poor catalytic performance caused by etching MAB phase materials under extreme environments, such as material corrosion, agglomeration, and phase change.
[0005] The purpose of the present invention is to provide application of the ternary layered solid acid nanosheet catalyst in catalysis of hydrogen evolution in alkaline water.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a ternary layered solid acid nanosheet catalyst comprises the following steps:
[0008] 1) taking a trace amount of strong acid to remove the surface oxide layer of the MAB phase precursor to obtain a front-end product;
[0009] 2) The front-end product is subjected to organic solvent roller milling for partial etching reaction to obtain an intermediate product MA 1- x B;
[0010] 3) The intermediate product is subjected to centrifugal drying to obtain a ternary layered solid acid nanosheet catalyst.
[0011] In certain specific embodiments, the mass ratio of the MAB phase precursor to the strong acid is (10-20):(1-3) mg / μL, and the mass ratio of the MAB phase precursor to the organic solvent is (100-200):(4-6) mg / mL.
[0012] In some specific embodiments, the MAB phase precursor is a molybdenum aluminum boron bulk powder.
[0013] In certain specific embodiments, it is characterized in that the strong acid is 40% hydrofluoric acid.
[0014] In certain specific embodiments, the roller milling treatment is performed under the following conditions: roller milling is performed at a rotation speed of 200-300 rpm at room temperature, and the reaction is maintained for 48-72 hours.
[0015] Furthermore, the method also includes washing, separating and drying the product after the roller milling treatment.
[0016] In certain specific embodiments, the organic solvent is a 10-25% tetramethylammonium hydroxide aqueous solution.
[0017] In certain specific embodiments, the conditions of the centrifugal drying treatment are: centrifugation at a speed of 6000-7000 rpm for 1-3 min, and continuous drying at a temperature of 50-60° C. for 2-6 h.
[0018] A ternary layered solid acid nanosheet catalyst prepared by the above-mentioned preparation method.
[0019] The application of the above-mentioned ternary layered solid acid nanosheet catalyst in the field of catalysis.
[0020] Compared with the prior art, the present invention has at least the following advantages:
[0021] 1) The preparation method of the ternary layered solid sodium acid flake catalyst provided by the present invention comprises the following steps: pre-treating the MAB phase precursor with a trace amount of strong acid to remove the oxide layer on the surface of the MAB phase precursor, and then mixing with an organic solvent and mechanically rolling the precursor at room temperature to partially etch the A atomic layer to form solid acid sites on the surface of the material. The acid radical ions are evenly distributed on the surface, so that the catalyst can form an acidic environment in an alkaline medium, thereby improving the alkaline HER catalytic performance.
[0022] 2) The ternary layered solid acid nanosheet catalyst of the present invention is suitable for the needs of high-performance electrolysis of alkaline water for hydrogen evolution; experimental results show that its catalytic performance is better than that of the untreated MAB phase precursor and the MAB phase material treated by high-temperature strong alkali etching. The preparation method is simple, the stability is high, the cost is low, and it has a wide range of application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0024] Figure 1 The intermediate product MA in Example 1 of the present invention 1-x Physical picture of B;
[0025] Figure 2 is the XRD pattern of the ternary layered solid acid nanosheet catalyst in Example 1 of the present invention;
[0026] Figure 3 This is a SEM image of the ternary layered solid acid nanosheet catalyst in Example 1 of the present invention;
[0027] Figure 4 TEM image of the ternary layered solid acid nanosheet catalyst in Example 1 of the present invention;
[0028] Figure 5 This is a scanning linear voltammetry curve of the ternary layered solid acid nanosheet catalyst in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0030] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0031] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0032] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0033] In the following embodiments, the molybdenum aluminum boron raw material has a purity of 88 wt %, which is specifically purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; the tetramethylammonium hydroxide aqueous solution raw material has a concentration of 25%, which is specifically purchased from Shanghai McLean Biochemical Technology Co., Ltd.; the hydrofluoric acid raw material has a concentration of 40%, which is specifically purchased from Chengdu Cologne Chemicals Co., Ltd.
[0034] Example 1
[0035] This embodiment provides a method for preparing a ternary layered solid acid nanosheet catalyst, comprising the following steps:
[0036] 1) Weigh 20 μl of hydrofluoric acid, add it to 100 mg of molybdenum aluminum boron bulk (MoAlB Bulk) powder, stir and mix to obtain a front-end product;
[0037] 2) Weigh 5 ml of 25% tetramethylammonium hydroxide aqueous solution, add it to the above-mentioned front-end product, mix it evenly, and then place it on a drum ball mill, roll mill it at a speed of 300 rpm at room temperature, and maintain the reaction for 72 hours to obtain the intermediate product MA 1-x B (actual picture as Figure 1 shown);
[0038] 3) The intermediate product MA 1-x B was placed in a 10 ml centrifuge tube, washed with deionized water and alcohol, and transferred to a high-speed centrifuge. The centrifuged product was centrifuged at 7000 rpm for 1 min to obtain a centrifugal product. The centrifugal product was then placed in a vacuum oven and dried at 60 ° C for 6 h. When the drying was completed and the temperature dropped to room temperature, the ternary layered solid acid nanosheet catalyst (MoAl 1-x B NS).
[0039] Example 2
[0040] This embodiment provides a method for preparing a ternary layered solid acid nanosheet catalyst, comprising the following steps:
[0041] 1) Weigh 10 μl of hydrofluoric acid, add it to 100 mg of molybdenum aluminum boron bulk powder (MoAlB Bulk), stir and mix to obtain a pretreated front-end product;
[0042] 2) Weigh 4 ml of 25% tetramethylammonium hydroxide aqueous solution, add it to the above-mentioned front-end product, mix it evenly, and then place it on a drum ball mill, roll mill it at a speed of 200 rpm at room temperature, and maintain the reaction for 72 hours to obtain the intermediate product MA 1-x B;
[0043] 3) The intermediate product MA 1-x B was placed in a 10 ml centrifuge tube, washed with deionized water and alcohol, and transferred to a high-speed centrifuge. The centrifuged product was centrifuged at 6000 rpm for 3 min to obtain a centrifugal product. The centrifugal product was then placed in a vacuum oven and dried at 60°C for 3 h. When the drying was completed and the temperature dropped to room temperature, the ternary layered solid acid nanosheet catalyst was collected.
[0044] Example 3
[0045] This embodiment provides a method for preparing a ternary layered solid acid nanosheet catalyst, comprising the following steps:
[0046] 1) Weigh 20 μl of hydrofluoric acid, add it to 150 mg of molybdenum aluminum boron bulk powder (MoAlB Bulk), stir and mix to obtain a pretreated front-end product;
[0047] 2) Weigh 6 ml of 15% tetramethylammonium hydroxide aqueous solution, add it to the above-mentioned front-end product, mix well, then place it on a drum ball mill, roll mill at 300 rpm at room temperature, maintain the reaction for 48 hours, and obtain the intermediate product MA 1-x B;
[0048] 3) The intermediate product MA 1-x B was placed in a 10 ml centrifuge tube, washed with deionized water and alcohol, and transferred to a high-speed centrifuge. The centrifuged product was centrifuged at 7000 rpm for 1 min to obtain a centrifugal product. The centrifugal product was then placed in a vacuum oven and dried at 50°C for 6 h. When the drying was completed and the temperature dropped to room temperature, the ternary layered solid acid nanosheet catalyst was collected.
[0049] Example 4
[0050] This embodiment provides a method for preparing a ternary layered solid acid nanosheet catalyst, comprising the following steps:
[0051] 1) Weigh 30 μl of hydrofluoric acid, add it to 200 mg of molybdenum aluminum boron bulk powder (MoAlB Bulk), stir and mix to obtain a pretreated front-end product;
[0052] 2) Weigh 6 ml of 15% tetramethylammonium hydroxide aqueous solution, add it to the above-mentioned front-end product, mix well, then place it on a drum ball mill, roll mill at 300 rpm at room temperature, maintain the reaction for 48 hours, and obtain the intermediate product MA 1-x B;
[0053] 3) The intermediate product MA 1-x B was placed in a 10 ml centrifuge tube, washed with deionized water and alcohol, and transferred to a high-speed centrifuge. The centrifuged product was centrifuged at 7000 rpm for 1 min to obtain a centrifugal product. The centrifugal product was then placed in a vacuum oven and dried at 60°C for 2 h. When the drying was completed and the temperature dropped to room temperature, the ternary layered solid acid nanosheet catalyst was collected.
[0054] Example 5
[0055] This embodiment provides a method for preparing a ternary layered solid acid nanosheet catalyst, comprising the following steps:
[0056] 1) Weigh 25 μl of hydrofluoric acid, add it to 150 mg of molybdenum aluminum boron bulk powder (MoAlB Bulk), stir and mix to obtain a pretreated front-end product;
[0057] 2) Weigh 5 ml of 15% tetramethylammonium hydroxide aqueous solution, add it to the above-mentioned front-end product, mix well, then place it on a drum ball mill, roll mill at 300 rpm at room temperature, maintain the reaction for 48 hours, and obtain the intermediate product MA 1-x B;
[0058] 3) The intermediate product MA 1-x B was placed in a 10 ml centrifuge tube, washed with deionized water and alcohol, and transferred to a high-speed centrifuge. The centrifuged product was centrifuged at 7000 rpm for 1 min to obtain a centrifugal product. The centrifugal product was then placed in a vacuum oven and dried at 60°C for 2 h. When the drying was completed and the temperature dropped to room temperature, the ternary layered solid acid nanosheet catalyst was collected.
[0059] Comparative Example 1:
[0060] This comparative example provides a method for preparing a layered nanosheet catalyst, comprising the following steps:
[0061] 1) Weigh 200 mg of molybdenum aluminum boron bulk powder (MoAlB Bulk), add it to 30 ml of a 10% potassium hydroxide strong base aqueous solution, stir evenly, and obtain a well-mixed front-end product;
[0062] 2) The front-end product was transferred to a 100 ml high-pressure reactor, and then placed in a forced air oven for hydrothermal reaction at 180° C. The reaction was maintained for 24 h to obtain the intermediate product MBenes;
[0063] 3) The intermediate product MBenes was cooled to room temperature, placed in a 10 ml centrifuge tube, washed with deionized water and alcohol, and transferred to a high-speed centrifuge. The product was centrifuged at 7000 rpm for 1 min to obtain a centrifuged product. The centrifuged product was then placed in a vacuum oven and dried at 60° C. for 6 h. When the drying was completed and the temperature dropped to room temperature, the layered nanosheet catalyst (MoB NS-2) was collected.
[0064] Comparative Example 2
[0065] This comparative example provides a layered nanosheet catalyst, whose components and proportions are basically the same as those in Example 1, except that the mass ratio of the MAB phase precursor to the volume of the strong acid is 10:4 mg / μL; and its process steps and parameters are the same as those in Example 1.
[0066] Comparative Example 3
[0067] This comparative example provides a layered nanosheet catalyst, whose components and proportions are basically the same as those in Example 1, except that the volume ratio of the mass of the MAB phase precursor to the organic solvent is 100:7 mg / mL; its process steps and parameters are the same as those in Example 1, and a layered nanosheet catalyst (MoB NS-1) is prepared.
[0068] Comparative Example 4
[0069] This comparative example provides a layered nanosheet catalyst, whose components and proportions are basically the same as those in Example 1, except that the mass ratio of the MAB phase precursor to the volume of the strong acid is 20:0.5 mg / μL; and its process steps and parameters are the same as those in Example 1.
[0070] Comparative Example 5
[0071] This comparative example provides a layered nanosheet catalyst, whose components and proportions are basically the same as those in Example 1, except that the volume ratio of the mass of the MAB phase precursor to the organic solvent is 200:3 mg / mL; and its process steps and parameters are the same as those in Example 1.
[0072] The present application tests the etching conditions of the layered nanosheet catalysts prepared in Comparative Examples 1-5, and finds that Comparative Examples 1, 2, and 3 are fully etched; while Comparative Examples 4 and 5 are partially etched, that is, the proportion of strong acid and organic solvent in the application is too large, and acid sites cannot be effectively formed; while the proportion of strong acid and organic solvent is too small, fewer acid sites are formed, and the catalytic performance cannot be improved.
[0073] The ternary layered solid acid nanosheet catalyst obtained by the preparation method of the present application is used in the electrolysis of water for hydrogen evolution.
[0074] Performance Test:
[0075] 1) Tissue morphology test
[0076] Taking Example 1 as an example, the intermediate product in the preparation method of the present invention, the obtained ternary layered solid acid nanosheet catalyst, was characterized by a field emission scanning electron microscope of Zeiss of Germany and a high-resolution powder X-ray diffractometer of Spectris of the United Kingdom. The results are as follows: Figure 1-Figure 4 As shown, Figure 1 The intermediate product MA 1-x B's physical picture, from Figure 1 It can be seen that the intermediate product is a uniform black suspension; Figure 2 The XRD pattern of the ternary layered solid acid nanosheet catalyst is shown in Figure 2. Figure 2 It can be seen that the physical phase is pure MoAlB; Figure 3 The SEM image of the ternary layered solid acid nanosheet catalyst is shown in Figure 2. Figure 3 It can be seen that the synthesized catalyst is layer-like; Figure 4 TEM image of the ternary layered solid acid nanosheet catalyst. Figure 4 It can be seen that the catalyst has reached the nanoscale.
[0077] 2) Electrochemical performance test
[0078] This application takes Example 1 as an example to test the electrochemical performance of the prepared ternary layered solid acid nanosheet catalyst, specifically:
[0079] The electrochemical tests were all conducted at room temperature using a CHI760E electrochemical workstation; the catalyst preparation method was as follows: 20 mg of sample was dispersed in a mixed solution of 870 μl of anhydrous ethanol, 100 μl of deionized water, and 30 μl of Nafion, and the solution was ultrasonicated in an ultrasonic cleaner to become a uniform ink-like state, and then 20 μl of the solution was dropped on the surface of the glassy carbon electrode using a pipette and dried, and 1M KOH (pH = 14) solution was used as an alkaline electrolyte for testing. A three-electrode system was used in the test, using a carbon rod as the counter electrode and Ag / AgCl as the reference electrode. The sample to be tested was titrated on the surface of the glassy carbon electrode (3 mm in diameter), and a scanning linear voltammetric curve test was performed, with a scanning speed of 0.1 mV and a potential range of (-0.8 to -1.8). The measured data was calibrated with a reversible hydrogen electrode (RHE) according to the equation:
[0080] E RHE =E Ag / AgCl +1.02V
[0081] Test results such as Figure 5 As shown in the figure, it can be seen that the ternary layered solid acid nanosheet (MoAl 1-x The onset potential of the ternary layered solid acid nanosheet catalyst is about 200 mV, which is lower than 300 mV of the untreated MAB phase bulk powder (MoAlB Bulk), the MAB phase material treated with an excessively high proportion of organic solvent (MoB NS-1), and 500 mV of the MAB phase material treated with high-temperature etching (MoB NS-2). This indicates that the performance of the ternary layered solid acid nanosheet catalyst is better than that of the untreated MAB phase bulk powder, as well as the MAB phase materials treated with high-temperature etching and excessively high proportion of organic solvent.
[0082] In summary: the preparation method of the ternary layered solid acid nanosheet catalyst proposed by the inventors is to select a suitable MAB phase precursor and a suitable organic solvent, and pre-treat the MAB phase precursor with a trace amount of strong acid, and then use a suitable organic solvent to roll-mill at room temperature to partially etch the A atomic layer, thereby forming solid acid sites on the surface of the material, and through the acid radical ions uniformly distributed on the surface, the catalyst can form an acidic environment in an alkaline medium, thereby improving the alkaline HER catalytic performance. The present invention provides a simple and mild method for synthesizing a ternary layered solid acid nanosheet catalyst, which can provide a new idea and method for synthesizing layered catalytic materials and improving the catalytic performance of catalysts.
[0083] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing a ternary layered solid acid nanosheet catalyst, characterized in that: The steps include: 1) taking a trace amount of strong acid to remove the surface oxide layer of the MAB phase precursor to obtain a front-end product; 2) The front-end product is subjected to organic solvent roller milling for partial etching reaction to obtain an intermediate product MA 1-x B; 3) The intermediate product is subjected to centrifugal drying to obtain a ternary layered solid acid nanosheet catalyst.
2. The method for preparing the ternary layered solid acid nanosheet catalyst according to claim 1, characterized in that: The mass ratio of the MAB phase precursor to the strong acid is (10-20):(1-3) mg / μL, and the volume ratio of the MAB phase precursor to the organic solvent is (100-200):(4-6) mg / mL.
3. The method for preparing the ternary layered solid acid nanosheet catalyst according to claim 1 or 2, characterized in that: The MAB phase precursor is molybdenum aluminum boron bulk powder.
4. The method for preparing the ternary layered solid acid nanosheet catalyst according to claim 1 or 2, characterized in that: The strong acid is 40% hydrofluoric acid.
5. The method for preparing the ternary layered solid acid nanosheet catalyst according to claim 1, characterized in that: The roller milling treatment conditions are: roller milling at a rotation speed of 200-300 rpm at room temperature, and maintaining the reaction for 48-72 hours.
6. The method for preparing the ternary layered solid acid nanosheet catalyst according to claim 5, characterized in that: The method also includes washing, separating and drying the product after the roller milling process.
7. The method for preparing the ternary layered solid acid nanosheet catalyst according to claim 6, characterized in that: The organic solvent is a 10-25% tetramethylammonium hydroxide aqueous solution.
8. The method for preparing the ternary layered solid acid nanosheet catalyst according to claim 1, characterized in that: The conditions of the centrifugal drying treatment are: centrifugation at a speed of 6000-7000 rpm for 1-3 minutes, and continuous drying at a temperature of 50-60° C. for 2-6 hours.
9. The ternary layered solid acid nanosheet catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the ternary layered solid acid nanosheet catalyst according to claim 9 in the field of catalysis.